What's That Smell? An Ecological Approach to Understanding Preferences for Familiar Odors. (January 2015) - Schloss, Karen B; Goldberger, Carolyn S; Palmer, Stephen E; Levitan, Carmel A
How do odor preferences arise? Following Palmer and Schloss's (2010, PNAS, 107, 8877–8882) ecological valence theory of color preferences, we propose that preference for an odor is determined by preferences for all objects and/or entities associated with that odor. The present results showed that preferences for familiar odors were strongly predicted by average preferences for all things associated with the odors (eg people liked the apple odor which was associated with mostly positive things, such as apples, soap, and candy, but disliked the fish odor, which was associated with mostly negative things, such as dead fish, trash, and vomit). The odor WAVEs (weighted affective valence estimates) performed significantly better than one based on preference for only the namesake object (eg predicting preference for the apple odor based on preference for apples). These results suggest that preferences for familiar odors are based on a summary statistic, coding the valence of previous odor-related experiences. We discuss how this account of odor preferences is consistent with the idea that odor preferences exist to guide organisms to approach beneficial objects and situations and avoid harmful ones.